2018
DOI: 10.1063/1.5049332
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced degradation variation in industrial multicrystalline PERC silicon solar cells

Abstract: , and Giso Hahn giso.hahn@uni-konstanz.deAbstract. Light and elevated temperature induced degradation (LeTID) varies significantly in multicrystalline PERC silicon solar cells, depending mainly on the solar cell processes. We show that despite high firing temperatures, LeTID can manifest itself in two different ways: 1) strong LeTID in good grains (jsc and Voc losses >7%rel.), or 2) low LeTID in good grains with stronger LeTID at dislocation clusters. Such LeTID at dislocation clusters is not only caused by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Finally, Figure C reveals that the degradation is rather uniform laterally in good grain areas, which is characteristic of LeTID . However, defect clusters show slightly stronger LeTID, as reported recently, which is even more pronounced in the acidic‐textured cells (Figure E,F).…”
Section: Resultssupporting
confidence: 89%
“…Finally, Figure C reveals that the degradation is rather uniform laterally in good grain areas, which is characteristic of LeTID . However, defect clusters show slightly stronger LeTID, as reported recently, which is even more pronounced in the acidic‐textured cells (Figure E,F).…”
Section: Resultssupporting
confidence: 89%
“…During the editorial process, the reviewers of the manuscript pointed on a difference between locations of the LeTID‐related defects reported in the present work and those presented in the previous publications. Namely, in several publications (see previous studies), it was indicated that the grain boundary (GB) locations are less subjected to the LeTID than the intragrain material, whereas in the present study locations with the higher VSD density were usually degraded more in comparison with the surrounding material. It should be noted that contrary, higher aptitude to LeTID for locations containing dislocations, was also reported previously (see the study by Krauss et al and references therein).…”
Section: Resultsmentioning
confidence: 44%
“…Due to this effect, estimation of recombination activity of GB (and VSD in general) by PL is hampered, and possible changes of GB activity in PL study are particularly smeared. This may be a reason that PL did not detect degradation on GBs in . In contrast, the injection of carriers during the EL is not affected by light scattering.…”
Section: Resultsmentioning
confidence: 94%
“…To analyze the spatially distributed defect density changes in the wafers with the defect‐engineering processes used in this study, relative recombination rate change (RRRC) maps were prepared. This was based on the approach by Lindroos et al., where normalized defect density maps were prepared subtracting the inverse lifetime maps of SiN x :H passivated wafers in different degradation stages . In a simplified approach, here the PL signal is assumed to be proportional to the excess carrier density and the net doping .…”
Section: Resultsmentioning
confidence: 99%